Production method of welding titanium plate structure for refining cathode roller
Through welding, cold pressing deformation and annealing heat treatment methods, the bright strip problem caused by the difference in weld structure and substrate structure is solved, and the significant refinement of welds and high-quality production of copper foil is achieved, with simple technology and low cost.
Patent Information
- Application Number
- CN202510055487.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2045-01-14
AI Technical Summary
During the welding and manufacturing of the cathode roller titanium cylinder sleeve, the difference between the weld structure and the substrate structure leads to a bright strip of copper foil, affecting high-quality and high-efficiency production.
The combination of welding, cold press deformation and annealing heat treatment is adopted to control the rolling passes and single deformation amount through X-shaped bevel few-pass welding and multi-pass cold rolling to achieve large deformation of the weld and refine grains.
Effectively refine the microstructure of each area of the weld, reduce the difference between the weld structure and the base material structure, improve the quality and production efficiency of copper foil, and have a simple process and low cost.
Smart Images

Figure BDA0005241297130000141 
Figure BDA0005241297130000151 
Figure HDA0005241297140000011
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of rare metal material modification, and particularly relates to a production method for a refined cathode roller welded titanium plate structure. Background Art
[0002] Electrolytic copper foil is one of the important materials in lithium-ion batteries (LIB), printed circuit boards (PCB) and chip packaging substrates (CPS). At present, according to the different production methods of copper foil, it can generally be divided into two categories: rolled copper foil and electrolytic copper foil. Rolled copper foil is an ingot made by smelting and casting pure copper. Subsequently, the base material is prepared through a series of processes such as hot rolling, cold rolling, and annealing. The prepared base material is then repeatedly rolled using a high-precision rolling mill to obtain the required copper foil thickness and quality. Electrolytic copper foil is manufactured by electrochemical deposition of copper ions in an electrolyte solution. Compared with the shortcomings of rolled copper foil, such as complex production process, complex equipment requirements, low production efficiency, and high cost, electrolytic copper foil has the following advantages: simple production process, minimal equipment cost, easy control of foil thickness accuracy, high production efficiency, and reduced total cost.
[0003] With the rapid development of downstream technology, the demand for electrolytic copper foil in the upstream is increasing year by year, especially the requirements for the quality of copper foil are getting higher and higher. The key equipment for producing copper foil is the cathode roller. The copper foil is generated by electroplating on the surface of the cathode roller, which is a continuation of the crystal structure of the cathode roller surface. The grade and quality of copper foil depends on the performance of the cathode roller surface material. The size of the grains on the surface of the cathode titanium roller, the smoothness and finish of the outer surface of the cathode roller titanium cylinder, and the surface roughness are crucial to the production of high-quality copper foil. Today, there are two main methods for manufacturing cathode rollers: spinning (seamless) and welding (with seams). The manufacturing cycle and process of spinning seamless cathode roller technology are long, expensive, and the spinning equipment and molds for manufacturing large-size diameter sleeves are too expensive. Compared with the spinning method, the welding method for preparing cathode roller titanium sleeves has the advantages of low cost, high production efficiency, and the manufacturing of titanium sleeves is not affected by diameter. Therefore, in the manufacture of large-diameter titanium cathode rollers, welding manufacturing methods are often required. However, due to the presence of a longitudinal weld on the surface of the cathode roller titanium sleeve during the welding production process, a bright band also exists at the corresponding position of the copper foil, which seriously affects and restricts the high-quality and high-efficiency production of copper foil.
[0004] There are some studies in the prior art on treating the weld to reduce the difference between the weld structure and the base material structure, thereby eliminating the periodic bright band printed on the foil by the weld structure. Among them, the manufacturing method of the titanium cathode roller body in CN200410026157 heats the weld and the heat-affected zone, and cools and protects the non-deformed base material part, upsets the weld and then forges it flat; then heats the weld and the heat-affected zone, and cools and protects the non-deformed base material part, upsets the weld and then forges it flat, repeats this process many times, deforms the weld many times, and the deformation amount each time should be more than 30%; and heat treats the deformed part. The present invention deforms the casting structure to change the casting structure into an equiaxed structure that is basically the same as the base material structure, has many process flows, and causes excessive energy consumption. CN202210103233 A method for preparing a wide-width fine-grained pure titanium plate for a cathode roller, which mainly emphasizes the first-time rolling, plate shape and surface treatment, blanking, second-time rolling, straightening, annealing, plate shape and surface treatment of the pure titanium slab to obtain a finished wide-width pure titanium fine-grained plate for a cathode roller. The process is relatively complicated, and there is no microstructure comparison in different areas of each weld. In "The influence of cold rolling on the structure and performance of industrial pure titanium plate welds", the plate is deformed by two cold rolling processes to reduce the grain size in the weld processing area. Although there are some studies on the refinement of grain structure by cold pressing + annealing, the specific problems faced are different for different products. The required thickness of the titanium plate for the cathode roller is 8mm. If a large deformation is achieved by one or two rollings, the deformation amount each time is very large. For thicker plates for cathode rollers, weld cracking is very likely to occur. "Research on the Crystallization Process of Titanium Welded Cathode Roller Weld Seam for Electrolytic Copper Foil" applies 60% to 70% processing deformation to the pure titanium welded cathode roller weld seam, and then performs heat treatment at T3 temperature. The weld seam structure reaches level 6. It can be seen that the structure is still coarse after refinement. The higher the grain refinement level, the more conducive it is to produce high-quality copper foil. At present, how to significantly refine the grains in each area of the weld seam to level 9 to 10 is very difficult. In the preparation method of CN200910213091.6 large titanium cathode roller, in order to solve the problem of high deformation resistance and easy defects, it adopts the traditional idea that heat treatment is performed after each deformation to relieve stress, resulting in a complex process and high energy consumption, and the cathode roller is pressed to refine the grains to level 8.
[0005] Therefore, how to control the rolling passes and the single deformation amount, adopt multi-pass cold pressing, and achieve large deformation of the weld while ensuring that the titanium plate weld does not crack, so as to achieve a significant effect of grain refinement, is the technical problem to be solved by the present invention. Summary of the invention
[0006] Based on the above technical problems, the present invention provides a production method for fine-grained cathode roller welded titanium plate structure. The present invention combines welding, cold pressing deformation and annealing heat treatment, adopts a coordinated treatment method of welding process and cold pressing deformation, has the advantages of simplicity, low cost, easy operation, and finally obtains good grain refinement effect.
[0007] The technical solution adopted by the present invention to solve the technical problem is: a production method for refining the structure of a welded titanium plate for a cathode roller, comprising the following steps:
[0008] (1) TA1 titanium plate was selected as the research object.
[0009] (2) Processing an X-shaped groove on the titanium plate.
[0010] (3) Pretreatment of titanium plate before welding
[0011] The welding wire is made of the same material as the parent material, and the specific composition is shown in Table 1. The joint adopts an X-shaped groove with a groove gap of 1mm and an angle of 70°. Pretreatment before welding: grind the test plate with a grinder, clean with acetone, and remove oil, dust, oxide film, etc. within 20mm on both sides of the weld; preheat the workpiece, preheat the test piece in a drying oven, and cool it to 50°C; tack welding, tack welding is performed after the alcohol is completely volatilized, and the weld gap is reserved for tack welding at both ends of the workpiece, with a reserved gap of 3mm at the top and 2mm at the bottom, and a reverse deformation of 1.5°.
[0012] Table 1 Chemical composition of welding wire wt.%
[0013] element C H N O Fe Ti content 0.01 0.0016 0.0015 0.029 0.03 Balance
[0014] (4) The titanium plate is subjected to welding, cold pressing and annealing heat treatment;
[0015] The pretreated X-groove titanium plate was welded, and the specific welding parameters were: welding current 115A, welding voltage 8-9V, welding speed 5.3cm / min, 5-9 passes, shielding gas was 99.99% purity argon, and weld height was 7.5-13mm.
[0016] Furthermore, the weld plate is rolled 8-11 times with a two-roll mill until the weld deformation is 59-65%, the deformation of the first 4 passes accounts for 70% of the total deformation, and the deformation of the first pass is close to 20%; the deformation of the last 4 to 7 passes accounts for 30% of the total deformation. After the rolling process is completed, the height of the weld plate is 2.15 to 4.55 mm.
[0017] As a preference, the deformation in the first four passes accounts for 70% of the total deformation, the deformation in the first pass is close to 20%, and the deformation in each subsequent pass gradually decreases (e.g., each pass is reduced by 1%-10% on the basis of the previous pass); the deformation in the last 4 to 7 passes accounts for 30% of the total deformation, and on the basis of the fourth pass, the deformation in each pass is further gradually reduced. After the rolling process is completed, the height of the weld plate is 2.15 to 4.55 mm.
[0018] The grains in the heat affected zone are obviously refined, and the X-shaped groove with fewer passes is more conducive to the refinement of the microstructure in the heat affected zone.
[0019] As the deformation amount increases and the deformation resistance increases, the present invention adjusts the rolling passes and the deformation amount of each pass to increase the total deformation of the weld while ensuring that the titanium plate weld does not crack, thereby ultimately achieving the effect of grain refinement.
[0020] The present invention adopts a few passes of welding + multiple passes of cold rolling + annealing, including a welding process using an X-shaped groove and few passes of welding, and obtains welds of different heights under different welding passes, which is more conducive to achieving the refinement of the grains in each area of the weld than the commonly used V-shaped groove welding. On this basis, the rolling passes and the single deformation amount are creatively used for coordinated regulation to obtain a finer grain size. The welding cold pressing treatment of the present invention is a process that combines different cold pressing deformation treatments under different welding processes. It is characterized in that welding and cold pressing treatment are combined together, and the two production processes jointly affect the microstructure of each area of the weld to achieve the refinement of the microstructure of each area of the weld. This method is simple in process and saves energy consumption and equipment investment.
[0021] Compared with the traditional hot rolling which needs to be performed above the recrystallization temperature, the risk of grain growth caused by the heating process can be effectively avoided, and the microstructure is refined at the same time. The present invention reduces energy consumption, can better refine the grains, improve its microstructure, and reduce the difference between the weld structure and the parent material structure.
[0022] Annealing conditions are: 600℃ annealing for 1h. Temperature or time lower than this is not conducive to recrystallization; temperature or time higher than this is likely to lead to grain growth and poor mechanical properties of the titanium plate.
[0023] (5) Sampling, testing and analysis of titanium plates after welding and cold pressing annealing. The test analysis specifically includes:
[0024] The cross-sectional microstructure was observed using a DMI-3000M optical microscope.
[0025] The inventive idea of the present invention:
[0026] In order to make the microstructure of each area of the weld closer to the microstructure of the parent material, the titanium plate is subjected to X-shaped groove welding with a few passes, cold pressing annealing heat treatment, and deformation treatment of the weld area compared with the traditional method. This method can better refine the grains during welding process adjustment. The present invention combines welding and cold pressing treatment. This process can achieve the refinement of the microstructure of each area of the weld while preparing the cathode roller, reduce costs, and has made great progress in refining the microstructure of each area of the weld compared with the traditional process.
[0027] The beneficial effects of the present invention are:
[0028] (1) The present invention adopts an optimized manual tungsten inert gas arc welding process, which avoids the problem of excessive coarsening of grains at welding temperature with fewer passes of X-shaped groove welding.
[0029] (2) The present invention adopts cold pressing deformation plus annealing heat treatment after welding. After multiple cold pressings with large deformation, annealing treatment can more effectively refine the grains, improve the performance of the weld, and reach a level basically consistent with the parent material. The effect of refining grains is better than conventional heat treatment, and the problem of grain growth during heating is avoided. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is the weld microstructure obtained in Example 1;
[0031] Figure 2 This is the weld microstructure obtained in Example 2;
[0032] Figure 3 This is the weld microstructure obtained in Example 3;
[0033] Figure 4 This is the weld microstructure obtained in Example 4;
[0034] Figure 5 This is the weld microstructure obtained in Example 5;
[0035] Figure 6 This is the weld microstructure obtained in Example 6;
[0036] Figure 7 This is the weld microstructure obtained in Example 7;
[0037] Figure 8 This is the weld microstructure obtained in Example 8;
[0038] Fig. 9 This is the weld microstructure obtained in Example 9;
[0039] Fig.10 is the weld microstructure obtained in Example 10;
[0040] Fig.11is the weld microstructure obtained in Example 11;
[0041] Fig.12 This is the weld microstructure obtained in Example 1. DETAILED DESCRIPTION
[0042] The present invention is further described below in conjunction with the accompanying drawings. The present invention is further described below in conjunction with embodiments, but is not limited thereto.
[0043] In the embodiment, the welding wire is made of the same material as the base material, with a diameter of Φ3mm and a specific composition of:
[0044] Table 1 Chemical composition of welding wire wt.%
[0045] element C H N O Fe Ti content 0.01 0.0016 0.0015 0.029 0.03 Balance
[0046] The joint form adopts an X-shaped groove with a groove gap of 1mm and an angle of 70° for multi-layer welding. Pretreatment before welding: grind the test plate with a grinder and clean it with alcohol or acetone to remove oil, dust, oxide film, etc. within 20mm on both sides of the weld; preheat the workpiece, preheat the test piece in a drying oven, and cool it to 50℃; positioning welding, positioning welding is performed after the alcohol is completely volatilized, and positioning welding is performed at both ends of the workpiece with a reserved weld gap, with a reserved gap of 3mm on the upper part and 2mm on the lower part, and a reverse deformation of 1.5°.
[0047] Example 1
[0048] (1) TA1 titanium plate was selected as the research object, and the specifications of the titanium plate were 80mm×30mm×8mm;
[0049] (2) Processing X-shaped grooves on two titanium plates by manual tungsten inert gas welding, with specific welding parameters: welding current 115A, welding speed 5.3cm / min, 6 passes, shielding gas 99.99% argon, weld height 8.6mm;
[0050] (3) The titanium plate after welding is subjected to cold pressing + annealing heat treatment. Before the test, the weld surface is ground to remove the surface oxide layer, and then wiped with acetone to remove oil stains to ensure that there is no slag on the weld surface. The welded test plate is placed under a two-roll mill with a roll speed of 1.6 rpm. The weld placement direction is parallel to the forward direction of the roll. 11 passes are rolled (the deformation of the first 4 passes accounts for about 70% of the total deformation, the deformation of the first pass is close to 20%, and the deformation of each pass gradually decreases thereafter; the deformation of the last 7 passes accounts for 30% of the total deformation, and the deformation of each pass is gradually reduced on the basis of the 4th pass) until the overall height of the weld plate reaches 3 mm and the weld stacking deformation is 65%. After cold pressing, annealing heat treatment is performed at 600°C for 1 hour;
[0051] (4) Samples were taken from the titanium plate after heat treatment, and the cross-sectional microstructure was observed using a DMI-3000M optical microscope.
[0052] Example 2
[0053] (1) TA1 titanium plate was selected as the research object, and the specifications of the titanium plate were 80mm×30mm×8mm;
[0054] (2) Processing X-shaped grooves on two titanium plates by manual tungsten inert gas welding, with specific welding parameters: welding current 115A, welding speed 5.3cm / min, number of layers 6, shielding gas 99.99% argon, weld height 8.6mm;
[0055] (3) The titanium plate after welding is subjected to cold pressing annealing heat treatment. Before the test, the weld surface is ground to remove the surface oxide layer, and then wiped with acetone to remove oil stains to ensure that there is no slag on the weld surface. The welded test plate is placed under a two-roll mill with a roll speed of 1.6 rpm. The weld placement direction is parallel to the forward direction of the roll. It is rolled for 10 passes (the deformation of the first 4 passes accounts for about 70% of the total deformation, the deformation of the first pass is close to 20%, and the deformation of each pass gradually decreases thereafter; the deformation of the last 6 passes accounts for 30% of the total deformation, and on the basis of the 4th pass, the deformation of each pass is further gradually reduced) until the overall height of the weld plate reaches 3.5 mm, and the weld stacking deformation is 59.3%. After cold pressing, it is annealed and heat treated at 600°C for 1 hour;
[0056] (4) Samples were taken from the titanium plate after heat treatment, and the cross-sectional microstructure was observed using a DMI-3000M optical microscope.
[0057] Example 3
[0058] (1) TA1 titanium plate was selected as the research object, and the specifications of the titanium plate were 80mm×30mm×8mm;
[0059] (2) Processing X-shaped grooves on two titanium plates by manual tungsten inert gas welding, with specific welding parameters: welding current 115A, welding speed 5.3cm / min, number of layers 7, shielding gas 99.99% argon, weld height 10.1mm;
[0060] (3) The titanium plate after welding is subjected to cold pressing annealing heat treatment. Before the test, the weld surface is ground to remove the surface oxide layer, and then wiped with acetone to remove oil stains to ensure that there is no slag on the weld surface. The welded test plate is placed under a two-roll rolling mill with a roll speed of 1.6 rpm. The weld placement direction is parallel to the forward direction of the roll. It is rolled for 10 passes (the deformation of the first 4 passes accounts for about 70% of the total deformation, the deformation of the first pass is close to 20%, and the deformation of each pass gradually decreases thereafter; the deformation of the last 6 passes accounts for 30% of the total deformation, and on the basis of the fourth pass, the deformation of each pass is further gradually reduced) until the overall height of the weld plate reaches 3.5 mm (the weld height deformation is 65%). After cold pressing, it is annealed and heat treated at 600°C for 1 hour;
[0061] (4) Samples were taken from the titanium plate after heat treatment, and the cross-sectional microstructure was observed using a DMI-3000M optical microscope.
[0062] Example 4
[0063] (1) TA1 titanium plate was selected as the research object, and the specifications of the titanium plate were 80mm×30mm×8mm;
[0064] (2) Processing X-shaped grooves on two titanium plates by manual tungsten inert gas welding, with specific welding parameters: welding current 115A, welding speed 5.3cm / min, number of layers 7, shielding gas 99.99% argon, weld height 10.1mm;
[0065] (3) The titanium plate after welding is subjected to cold pressing annealing heat treatment. Before the test, the weld surface is ground to remove the surface oxide layer, and then wiped with acetone to remove oil stains to ensure that there is no slag on the weld surface. The welded test plate is placed under a two-roll rolling mill with a roll speed of 1.6 rpm. The weld placement direction is parallel to the forward direction of the roll. The plate is rolled in 9 passes to the overall height of the weld plate (the deformation of the first 4 passes accounts for about 70% of the total deformation, the deformation of the first pass is close to 20%, and the deformation of each pass gradually decreases thereafter; the deformation of the last 5 passes accounts for 30% of the total deformation, and on the basis of the fourth pass, the deformation of each pass is further gradually reduced) to 4 mm (the weld height deformation is 60%). After cold pressing, the plate is annealed at 600°C for 1 hour;
[0066] (4) Samples were taken from the titanium plate after heat treatment, and the cross-sectional microstructure was observed using a DMI-3000M optical microscope.
[0067] Example 5
[0068] (1) TA1 titanium plate was selected as the research object, and the specifications of the titanium plate were 80mm×30mm×8mm;
[0069] (2) Processing X-shaped grooves on two titanium plates by manual tungsten inert gas welding, with specific welding parameters: welding current 115A, welding speed 5.3cm / min, 8 welding passes, shielding gas 99.99% argon, weld height 11.5mm;
[0070] (3) The titanium plate after welding is subjected to cold pressing annealing heat treatment. Before the test, the weld surface is ground to remove the surface oxide layer, and then wiped with acetone to remove oil stains to ensure that there is no slag on the weld surface. The welded test plate is placed under a two-roll rolling mill with a roll speed of 1.6 rpm. The weld placement direction is parallel to the forward direction of the roll. The plate is rolled in 9 passes to the overall height of the weld plate (the deformation of the first 4 passes accounts for about 70% of the total deformation, the deformation of the first pass is close to 20%, and the deformation of each pass gradually decreases thereafter; the deformation of the last 5 passes accounts for 30% of the total deformation, and on the basis of the fourth pass, the deformation of each pass is further gradually reduced) to 4 mm (the weld height deformation is 65%). After cold pressing, the plate is annealed at 600°C for 1 hour;
[0071] (4) Samples were taken from the titanium plate after heat treatment, and the cross-sectional microstructure was observed using a DMI-3000M optical microscope.
[0072] Example 6
[0073] (1) TA1 titanium plate was selected as the research object, and the specifications of the titanium plate were 80mm×30mm×8mm;
[0074] (2) Processing X-shaped grooves on two titanium plates by manual tungsten inert gas welding, with specific welding parameters: welding current 115A, welding voltage 8-9V, welding speed 5.3cm / min, 8 passes, shielding gas 99.99% argon, weld height 11.5mm;
[0075] (3) The titanium plate after welding is subjected to cold pressing annealing heat treatment. Before the test, the weld surface is ground to remove the surface oxide layer, and then wiped with acetone to remove oil stains to ensure that there is no slag on the weld surface. The welded test plate is placed under a two-roll rolling mill with a roller speed of 1.6 rpm. The weld placement direction is parallel to the forward direction of the roller. The plate is rolled in 8 passes to the overall height of the weld plate (the deformation of the first 4 passes accounts for about 70% of the total deformation, the deformation of the first pass is close to 20%, and the deformation of each pass gradually decreases thereafter; the deformation of the last 4 passes accounts for 30% of the total deformation, and on the basis of the fourth pass, the deformation of each pass is further gradually reduced) to 4.5 mm (the weld height deformation is 61%). After cold pressing, the plate is annealed at 600°C for one hour;
[0076] (4) Samples were taken from the titanium plate after heat treatment, and the cross-sectional microstructure was observed using a DMI-3000M optical microscope.
[0077] Example 7
[0078] (1) TA1 titanium plate was selected as the research object, and the specifications of the titanium plate were 80mm×30mm×8mm;
[0079] (2) Processing X-shaped grooves on two titanium plates by manual tungsten inert gas welding, with specific welding parameters: welding current 115A, welding voltage 8-9V, welding speed 5.3cm / min, 9 passes, shielding gas 99.99% argon, weld height 13mm;
[0080] (3) The titanium plate after welding is subjected to cold pressing annealing heat treatment. Before the test, the weld surface is ground to remove the surface oxide layer, and then wiped with acetone to remove oil stains to ensure that there is no slag on the weld surface. The welded test plate is placed under a two-roll rolling mill with a roll speed of 1.6 rpm. The weld placement direction is parallel to the forward direction of the roll. Eight passes are rolled to the overall height of the weld plate (the deformation of the first four passes accounts for about 70% of the total deformation, the deformation of the first pass is close to 20%, and the deformation of each pass gradually decreases thereafter; the deformation of the last four passes accounts for 30% of the total deformation, and on the basis of the fourth pass, the deformation of each pass is further gradually reduced) to 4.5 mm (the weld height deformation is 65%), and annealed at 600°C for 1 hour after cold pressing;
[0081] (4) Samples were taken from the titanium plate after heat treatment, and the cross-sectional microstructure was observed using a DMI-3000M optical microscope.
[0082] Embodiment 8:
[0083] The difference between Example 8 and Example 1 is that the annealing temperature is different.
[0084] (1) TA1 titanium plate was selected as the research object, and the specifications of the titanium plate were 80mm×30mm×8mm;
[0085] (2) Processing X-shaped grooves on two titanium plates by manual tungsten inert gas welding, with specific welding parameters: welding current 115A, welding voltage 8-9V, welding speed 5.3cm / min, welding, 6 passes, shielding gas 99.99% argon, weld height 8.6mm;
[0086] (3) The titanium plate after welding is subjected to cold pressing annealing heat treatment. Before the test, the weld surface is ground to remove the surface oxide layer, and then wiped with acetone to remove oil stains to ensure that there is no slag on the weld surface. The welded test plate is placed under a two-roll rolling mill with a roll speed of 1.6 rpm. The weld placement direction is parallel to the forward direction of the roll. 11 passes are rolled (the deformation of the first 4 passes accounts for about 70% of the total deformation, the deformation of the first pass is close to 20%, and the deformation of each pass gradually decreases thereafter; the deformation of the last 7 passes accounts for 30% of the total deformation, and on the basis of the fourth pass, the deformation of each pass is further gradually reduced). The plate is rolled until the overall height of the weld plate reaches 3 mm (the weld height deformation is 65%). After cold pressing, the plate is annealed and heat treated at 650°C for 1 hour.
[0087] (4) Samples were taken from the titanium plate after heat treatment, and the cross-sectional microstructure was observed using a DMI-3000M optical microscope.
[0088] Example 9
[0089] (1) TA1 titanium plate was selected as the research object, and the specifications of the titanium plate were 80mm×30mm×8mm;
[0090] (2) Processing X-shaped grooves on two titanium plates by manual tungsten inert gas welding, with specific welding parameters: welding current 115A, welding speed 5.3cm / min, number of layers 6, shielding gas 99.99% argon, weld height 8.6mm;
[0091] (3) The titanium plate after welding is subjected to cold pressing annealing heat treatment. Before the test, the weld surface is ground to remove the surface oxide layer, and then wiped with acetone to remove oil stains to ensure that there is no slag on the weld surface. The welded test plate is placed under a two-roll rolling mill with a roll speed of 1.6 rpm. The weld placement direction is parallel to the forward direction of the roll. 11 passes are rolled (the deformation of the first 4 passes accounts for about 70% of the total deformation, the deformation of the first pass is close to 20%, and the deformation of each pass gradually decreases thereafter; the deformation of the last 7 passes accounts for 30% of the total deformation, and on the basis of the fourth pass, the deformation of each pass is further gradually reduced). The overall height of the rolled weld plate is 2.15 mm, and the weld height deformation is 75%. After cold pressing, it is annealed and heat treated at 600°C for 1 hour;
[0092] (4) Samples were taken from the titanium plate after heat treatment, and the cross-sectional microstructure was observed using a DMI-3000M optical microscope.
[0093] When the deformation amount of Example 1 is 65%, the microstructure refinement effect of each area of the weld is significant, and the structures of the weld area and the heat-affected zone are indistinguishable, and the invention goal has been achieved. However, Example 9 further increases the deformation amount, which increases the cost, and the thickness of the cathode roller is too thin, which affects the performance of use and is prone to cracking.
[0094] Example 10
[0095] (1) TA1 titanium plate was selected as the research object, and the specifications of the titanium plate were 80mm×30mm×8mm;
[0096] (2) Processing X-shaped grooves on two titanium plates by manual tungsten inert gas welding, with specific welding parameters: welding current 115A, welding speed 5.3cm / min, number of layers 6, shielding gas 99.99% argon, weld height 8.6mm;
[0097] (3) The titanium plate after welding is subjected to cold pressing annealing heat treatment. Before the test, the weld surface is ground to remove the surface oxide layer, and then wiped with acetone to remove oil stains to ensure that there is no slag on the weld surface. The welded test plate is placed under a two-roll mill with a roll speed of 1.6 rpm. The weld placement direction is parallel to the roll forward direction. 13 passes are rolled until the overall height of the weld plate reaches 3 mm, and the weld stacking deformation is 65%. After cold pressing, annealing heat treatment is performed at 600°C for 1 hour;
[0098] (4) Samples were taken from the titanium plate after heat treatment, and the cross-sectional microstructure was observed using a DMI-3000M optical microscope.
[0099] In Example 1, the goal of thinning each area of the weld has been achieved, and there is no need to increase the number of rolling passes and increase production costs.
[0100] Embodiment 11
[0101] Compared with Example 1, Example 11 has the following difference: the weld stack is lower, and other operations are the same.
[0102] (1) TA1 titanium plate was selected as the research object, and the specifications of the titanium plate were 80mm×30mm×8mm;
[0103] (2) Processing X-shaped grooves on two titanium plates by manual tungsten inert gas welding, with specific welding parameters: welding current 115A, welding speed 5.3cm / min, number of layers 5, shielding gas 99.99% argon, weld height 7.5mm;
[0104] (3) The titanium plate after welding is subjected to cold pressing annealing heat treatment. Before the test, the weld surface is ground to remove the surface oxide layer, and then wiped with acetone to remove oil stains to ensure that there is no slag on the weld surface. The welded test plate is placed under a two-roll rolling mill with a roll speed of 1.6 rpm. The weld placement direction is parallel to the forward direction of the roll. 11 passes are rolled until the overall height of the weld plate reaches 2.6 mm, and the weld stacking deformation is 65%. After cold pressing, annealing heat treatment is performed at 600°C for 1 hour;
[0105] (4) Samples were taken from the titanium plate after heat treatment, and the cross-sectional microstructure was observed using a DMI-3000M optical microscope.
[0106] In Example 11, the number of welding passes is small, and the weld pile height is reduced, which is not conducive to post-cold pressing treatment, is prone to defects, and is not conducive to grain refinement.
[0107] Comparative Example 1
[0108] (1) TA1 titanium plate was selected as the research object, and the specifications of the titanium plate were 80mm×30mm×8mm;
[0109] (2) Manual tungsten inert gas arc welding was used for the X-shaped groove. The specific welding parameters were as follows: welding current 115A, welding voltage 8-9V, welding speed 5.3cm / min, 6 passes, shielding gas 99.99% argon, and weld height 8.6mm;
[0110] (3) The titanium plate after welding is subjected to cold pressing annealing heat treatment. Before the test, the weld surface is ground to remove the surface oxide layer, and then wiped with acetone to remove oil stains to ensure that there is no slag on the weld surface. The welded test plate is cold pressed to a height of 3 mm (the weld height deformation is 65%), and then annealed at 600°C for 1 hour after cold pressing;
[0111] (4) Samples were taken from the titanium plate after heat treatment, and the cross-sectional microstructure was observed using a DMI-3000M optical microscope.
[0112] Table 3 Grain grade of weld and heat affected zone under different processes
[0113]
[0114]
[0115] By comparing the grain size grades of the weld zone and the heat affected zone of the welded plate under different process conditions, it can be seen that compared with the welded plate obtained by the conventional production process, after the welding process and the cold pressing process are adjusted and processed, and after the annealing heat treatment, the grain grade of the weld zone of Example 1 is 9-10, and the grain grade of the heat affected zone is 8.5-10, the grain grade of the weld zone of Example 2 is 8.5-9, and the grain grade of the heat affected zone is 8-9, the grain grade of the weld zone of Example 3 is 8-9, and the grain grade of the heat affected zone is 7.5-9, the grain grade of the weld zone of Example 4 is 7.5-9, and the grain grade of the heat affected zone is 7-9, the grain grade of the weld zone of Example 5 is 7.5-9, and the grain grade of the heat affected zone is 7-9, the grain grade of the weld zone of Example 6 is 7-9, and the grain grade of the heat affected zone is 6.5-9, the grain grade of the weld zone of Example 7 is 7-10, and the grain grade of the heat affected zone is 7.5-9. The grain grade of the weld zone of Example 8 is 8.5-9, and the grain grade of the heat affected zone is 8-9. The grain grade of the weld zone of Example 9 is 9-10, and the grain grade of the heat affected zone is 8.5-10. The grain grade of the weld zone of Example 10 is 9-10, and the grain grade of the heat affected zone is 8.5-10. The grain grade of the weld zone of Example 11 is 8.5-9, and the grain grade of the heat affected zone is 8- 9, the grain grade of the weld zone of comparative example 1 is 6.5-9, the grain grade of the heat affected zone is 6-9, the overall grain size difference of the weld plate is gradually reduced, and the grain difference of each region is also gradually reduced, and the grain size of the weld zone of comparative example 1 is increased from 6.5-9 to 9-10 in the weld zone of embodiment 1, and the grain size of the heat affected zone of comparative example 1 is increased from 6-9 to 8.5-10 in embodiment 1, and the grain size difference of each region is reduced. That is, welding and cold pressing annealing heat treatment can better refine the grains, improve its microstructure, and reduce the difference between the weld structure and the parent material structure (9-10).
[0116] from Figures 1 to 8 It can be found that the coarse columnar grains in the weld are refined after welding, cold pressing and annealing heat treatment. For X-shaped groove, fewer welding passes, with the increase of deformation under multi-pass rolling, the needle-shaped secondary α phase structure in the weld zone and heat-affected zone after annealing is more similar to the parent material in morphology, further reducing the difference between the weld structure and the parent material structure. Among them, the manual tungsten inert gas arc welding is welded for 6 passes, and the grain size of the weld zone and heat-affected zone after annealing is most similar to the parent material when the deformation is 65% under 11 passes of rolling.
[0117] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A method for producing a thinned cathode roller welded titanium plate structure, characterized in that: The process steps of the method are as follows: (1) Select TA1 titanium plate and use a milling machine to process an X-shaped groove on the titanium plate; (2) The welding wire is made of the same material as the titanium plate base material, and the titanium plate is welded 5 to 9 times by manual tungsten inert gas arc welding. The weld height after welding is 7.5 to 13 mm; (3) The welded titanium plate is subjected to multiple cold pressing and annealing heat treatments: the welded titanium plate is subjected to 8-11 cold pressing deformations until the weld deformation is 59-65%, and then subjected to 600-650°C insulation annealing heat treatment.
2. The method for producing a thinned cathode roller welded titanium plate structure according to claim 1, characterized in that: In the step (1), the dimensions of the X-shaped groove processed on the titanium plate are a gap of 1 mm and an angle of 70°.
3. The method for producing a thinned cathode roller welded titanium plate structure according to claim 1, characterized in that: Pretreatment before welding includes grinding the test plate with a grinder, cleaning with acetone, and removing oil, dust, and oxide film within 20mm on both sides of the weld. Preheat the workpiece in a drying oven and cool it to 50℃. Position welding is performed after the alcohol is completely evaporated. Position welding is performed at both ends of the workpiece with a reserved weld gap, with a 3mm gap reserved at the top and a 2mm gap reserved at the bottom, and a reverse deformation of 1.5°.
4. The method for producing a thinned cathode roller welded titanium plate structure according to claim 1, characterized in that: The welding process in step (2) is as follows: a welding current of 115A, a welding voltage of 8-9V, a welding speed of 5.3cm / min, and a shielding gas of 99.99% argon.
5. The method for producing a thinned cathode roller welded titanium plate structure according to claim 1, characterized in that: The deformation in the first four passes accounts for 70% of the total deformation, and the deformation in the first pass is close to 20%; the deformation in the last 4 to 7 passes accounts for 30% of the total deformation. After the rolling process is completed, the height of the weld plate is 2.15 to 4.55 mm.
6. The method for producing a thinned cathode roller welded titanium plate structure according to claim 1, characterized in that: The roller speed was 1.6 rpm, and the annealing heat treatment was performed at 600° C. for 1 hour.
Citation Information
Patent Citations
Preparation method of large titanium-cathode roller
CN101701351A
A method for preparing a wide-width, fine-grained pure titanium plate for cathode rollers.
CN114515758B
Method for making titanium cathode roller member
CN1283845C
Method for producing seamless titanium and titanium alloy welded pipe
CN102581062A
Production method for improving structure and performance of titanium material weld zone
CN115121917A